Simulation of Gain Narrowing for Near-Infrared Ultrashort Pulses - Springer, Ramon; Pflaum, Christoph (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
Within this work, a novel chromatic amplification model for ultrashort pulses is presented. By performing a modified Wigner transform including the Kaiser window function, a time-frequency correlation is obtained that contains only positive values. The positive value range enables the physical correct amplification and propagation of the Wigner distribution in gain media with nonlinear gain bandwidth. To demonstrate the applicability to ultrashort pulses, the presented model is used to simulate a Ho:YAG regenerative amplifier. In this particular example, pulses with a spectral range of 30 nm are seeded into the cavity and amplified from the nanojoule to the millijoule level. As a result of the proposed modeling technique, pulse energy and spectral changes during amplification could be precisely calculated. The simulated results are in well agreement with experimental measurements.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Chromatic Amplification; Ho:YAG; Regenerative Amplifier; Ultrashort Pulses; Wigner Distribution